Women's preferred futures. (Futurist)
In a cover story, women present scenarios of what they want their families, communities, and societies to be like in 2020. Many of the scenarios share several elements of a preferred future, including the end of glass ceilings, equal representation of the sexes at all levels of government, understanding and celebration of gender differences and diversity of all kinds, acceptance of single status, control over childbirth, community- and business-based child care, human-scaled institutions, equal education for women worldwide, a clean environment based on principles of sustainability, and less war, crime, and violence in general.